ANALISIS VOLATILITAS HARGA KOMODITAS UNGGULAN KABUPATEN KARO - Fauzul Azhimah; Chaula Lutfia Saragih; Hagai Bastanta KaroSekali; Eko Prasetya Ginting (Universitas Quality, 2023)
Karo Regency has several superior commodities, such as tomatoes, cabbage, carrots, red chilies, potatoes and mustard greens. The price of these commodities fluctuated due to shocks in demand and supply. Shock demand and supply cause price volatility in these superior commodities. Therefore, research was carried out by analyzing the retail price volatility of superior commodities in Karo Regency. Analysis of the volatility of commodity retail prices can illustrate the size of the risks that will be faced by economic actors in the future. The aim of the study was to determine the volatility of the retail price of Karo Regency's leading commodities such as tomatoes, cabbage, carrots, red chilies, potatoes and mustard greens. This research method uses the ARCH method with the ARIMA estimation model. The data used is secondary data from the karo district market service. The results showed that the volatility analysis was carried out on the 1st difference data, the estimation of the ARIMA model for tomatoes was carried out on ARIMA 5.1.1, cabbage 2.1.1, carrots 6.1.1, potatoes 0.1.1, red chilies 2.1.1 and mustard greens 1.1.1. All ARIMA models for these commodities have an ARCH effect, and based on the ARCH estimation model, cabbage and red chili show parameters > 1, while tomatoes, carrots, potatoes and mustard greens show parameters < 1. In conclusion, cabbage and red chilies have very high price volatility, while tomatoes, carrots, potatoes and mustard greens have low price volatility.